DEVELOPMENT AND EVALUATION OF VALUE ADDED MAIZE DALIA - SUBHA ROY; USHA SINGH; PRAMILA PRASAD (The Bioscan, 2020)
Value added maize dalia developed along with green gram dal and sweet potato is an energy and protein rich product. The energy and protein content of dalia was 687 kcal and 23.77g per 100 g respectively. The micronutrients such as calcium, riboflavin and niacin were 43.67 mg, 0.32mg and 1.42mg per 100 g respectively. The product being rich in macronutrients and micronutrients is recommended for eradication of protein energy malnutrition among women and children.